EVOLUSI TEKNOLOGI DI KOMUNITAS BADUY: KAJIAN HISTORIS DAN SOSIAL BADUY - Ekoh Saikoh; Nazla; Ujang Jamaludin; Ila Rosmilawati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This article examines the evolution of technology in the Baduy community as a process of cultural adaptation to historical and social changes. The Baduy community, known for its independence and restrictions on modern technology, shows how traditional technologies, such as self-sustaining agriculture and herbal medicine, evolved from pre-colonial to contemporary times without neglecting customs and harmony with nature. This research aims to analyze the historical development of technology, forms of social adaptation, its impact on social, economic, and cultural identity structures, and its implications for social studies education. The research uses a qualitative approach with secondary data from BPS (2020), BPNB (2015), and Millie (2009), as well as primary data through interviews with key informants and field observations. The validity of the data is strengthened through triangulation. The results show that the evolution of Baduy technology took place through hybridization between traditional practices and selective adaptation, characterized by resistance to modern technology and limited accommodations to herbal medicine and weaving production. This process has an impact on strengthening communal solidarity, economic independence, and the sustainability of cultural identity. The implications of the study emphasize the importance of integrating the Baduy case study in social studies learning to encourage active learning and social empathy. Thus, the evolution of Baduy technology can be understood as a model of cultural resilience in the midst of globalization.